2018
DOI: 10.1097/corr.0000000000000514
|View full text |Cite
|
Sign up to set email alerts
|

Acetabular Retroversion and Decreased Posterior Coverage Are Associated With Sports-related Posterior Hip Dislocation in Adolescents

Abstract: Background Leverage of the femoral head against the acetabular rim may lead to posterior hip dislocation during sports activities in hips with femoroacetabular impingement (FAI) deformity. Abnormal concavity of the femoral head and neck junction has been well described in association with posterior hip dislocation. However, acetabular morphology variations are not fully understood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
37
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 25 publications
3
37
1
Order By: Relevance
“…In the normal hip, that force is directed into bony structures but with acetabular retroversion, the force would be partially distributed into tissues such as the labrum. Acetabular retroversion and FAI are known to be associated with traumatic posterior hip dislocation in athletes, indicating that during activity there can be posteriorly directed forces . Finite element analysis of basic mobility activities in people with acetabular retroversion indicated that during chair rise there is greater posterior hip joint reaction force than in the normal hip where the force is distributed over a wider area of the acetabulum .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the normal hip, that force is directed into bony structures but with acetabular retroversion, the force would be partially distributed into tissues such as the labrum. Acetabular retroversion and FAI are known to be associated with traumatic posterior hip dislocation in athletes, indicating that during activity there can be posteriorly directed forces . Finite element analysis of basic mobility activities in people with acetabular retroversion indicated that during chair rise there is greater posterior hip joint reaction force than in the normal hip where the force is distributed over a wider area of the acetabulum .…”
Section: Discussionmentioning
confidence: 99%
“…Acetabular retroversion and FAI are known to be associated with traumatic posterior hip dislocation in athletes, indicating that during activity there can be posteriorly directed forces. [60][61][62][63] Finite element analysis of basic mobility activities in people with acetabular retroversion indicated that during chair rise there is greater posterior hip joint reaction force than in the normal hip where the force is distributed over a wider area of the acetabulum. 57 Performance of any type of squatting would certainly increase the posterior hip joint force in the hip with acetabular retroversion.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the findings from the current study, gaps in our knowledge and several questions remain. Although Novais and colleagues evaluated morphology [8], the mechanics of the hip joint must be considered from both the femoral and acetabular perspective. A combined assessment of femoral headneck concavity and femoral version plus the acetabular analysis of data from the current study is needed given the possibility of a fulcrum effect.…”
Section: Where Do We Need To Go?mentioning
confidence: 99%
“…n their analysis, Novais and colleagues [8] compared the postreduction CT scans of adolescents with sports-related posterior hip dislocation to CT scans of age-and gendermatched controls that had been obtained for suspected appendicitis. Only 27 patients (over the course of 16 years at a tertiary referral center) met the study criteria, demonstrating the infrequency of this injury.…”
mentioning
confidence: 99%
See 1 more Smart Citation